Clinical characteristics and management of immune checkpoint inhibitor-related cardiotoxicity: A single-center experience - Xiao, Junjuan; Li, Xingyu; Wang, Xuan; Guan, Yaping; Liu, Hairong; Liang, Jing; Li, Yan; Wang, Baocheng; Wang, Jun (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy that amplify T-cells-mediated immune responses by disrupting the immunoinhibitory signals in the past decade. The augmented T cells immune response has led to a range of immune-related adverse effects (irAEs). Immune-related cardiotoxicity have been reported in case series but have been underappreciated due to difficulties in diagnosis. This article describes the data of epidemiology, clinical presentation, subtypes, treatment, and a new systematic framework for clinical management of cardiotoxicity. METHODS: Data were abstracted for cancer patients who received ICIs in a single center between January 1, 2020, and February 28, 2022. ICI-associated cardiotoxicity was clinically diagnosed based on clinical presentations, biochemical biomarkers, and imaging features. RESULTS: We identified a total of 12 (2.46%) cases with ICI-related cardiotoxicity from 487 patients who received PD-1 or PD-L1 inhibitors. All patients were diagnosed with advanced or metastatic solid tumors. The severity of ICI-related cardiotoxicity ranged from subclinical cardiac abnormalities (subclinical type) with only asymptomatic troponin-I (TnI) elevations (25.0%) to symptomatic cardiac abnormalities (clinical type) (75.0%). Patients with symptomatic cardiac abnormalities had several manifestations including tachyarrhythmia (16.7%), bradyarrhythmia (41.7%), or cardiac failure (8.3%). Median immunotherapy exposure time was 1.5 doses (range: 1 to 5) and median time of the initial immunotherapy to onset of ICI-related cardiotoxicity was 33.5 day (IQR: 20.3 to 46.8). Most cases including those with subclinical cardiac abnormalities were administrated with systemic corticosteroid (58.3%). One (8.3%) patient was put on mechanical ventilation, one (8.3%) received the plasma exchange therapy, one (8.3%) was implanted with a pacemaker, and one (8.3%) was admitted to ICU. Three patients with symptomatic cardiac abnormalities (25.0%) died, and other patients presented significant clinical improvement with good outcome. CONCLUSIONS: ICI-related cardiotoxicity is uncommon but critical with high mortality rate and poor prognosis, especially for a small group of patients with symptomatic cardiac abnormalities. Based on the results from this real-world study, more attention should be paid to cardiotoxicity associated with ICIs, including baseline examinations and biochemical analyses before the initiation of immunotherapy, accurate and rapid diagnosis, and timely multi-disciplinary management with immunosuppressive agents and other necessary clinical interventions.